Hydro-meteorological hazards, risks, and disaster - Shroder, John F.; Paron, Paolo; Di Baldassarre, Giuliano 1978- (Hazards and disasters series, 2015)
Hydro-Meteorological Hazards, Risks, and Disasters provides an integrated look at major atmospheric disasters that have had and continue to have major implications for many of the world’s people, such as floods and droughts. . This volume takes a geoscientific approach to the topic, while also covering current thinking about some directly relevant social scientific issues that can affect lives and property. Hydro-Meteorological Hazards, Risks, and Disasters also contains new insights about how climate change affects hazardous processes. For the first time, information on the many diverse topics relevant to professionals is aggregated into one volume.--Provided by publisher.